SFRP1 Negatively Modulates Pyroptosis of Fibroblast‐Like Synoviocytes in Rheumatoid Arthritis: A Review - Jiang, Ping; Wei, Kai; Chang, Cen; Zhao, Jianan; Zhang, Runrun; Xu, Lingxia; Jin, Yehua; Xu, Linshuai; Shi, Yiming; Guo, Shicheng; Schrodi, Steven J.; He, Dongyi (Frontiers in Immunology, 2022)
Secreted frizzled-related protein 1 (SFRP1) is a member of secretory glycoprotein SFRP family. As a primitive gene regulating cell growth, development and transformation, SFRP1 is widely expressed in human cells, including various cancer cells and fibroblast-like synoviocytes (FLS) of rheumatoid arthritis (RA). Deletion or silencing of SFRP1 involves epigenetic and other mechanisms, and participates in biological behaviors such as cell proliferation, migration and cell pyroptosis, which leads to disease progression and poor prognosis. In this review, we discuss the role of SFRP1 in the pathogenesis of RA-FLS and summarize different experimental platforms and recent research results. These are helpful for understanding the biological characteristics of SFRP1 in RA, especially the mechanism by which SFRP1 regulates RA-FLS pyroptosis through Wnt/β-catenin and Notch signaling pathways. In addition, the epigenetic regulation of SFRP1 in RA-FLS is emphasized, which may be considered as a promising biomarker and therapeutic target of RA.